Diseño de un sistema contable en el centro de mecanización unión y trabajo, Cantón Salcedo Parroquia Mulalillo - Chicaiza Arias, Santiago Wladimir (2019)
It is important that "Union and mechanization work Center" from Salcedo Canton, Mulalillo Parish has an accounting system to the administrative and financial management which was determined by a diagnosis that gave a clear picture of the problem. To justify the research, the lack of control of the accounting records were analyzed to get better management of the economic resources. The purpose of this project is to design an accounting system to manage and control of the economic resources in order to apply it in an efficient way at the moment of making decisions, so the administrative and financial management will be improved within the organization. Bibliographic and documentary collection were used as methods of research; to get trustworthy resources about the accounting process techniques such as survey, interview, and view guidelines were applied to directors and users of Union and mechanization work Center to get information about economic transactions that are made daily. The competencies linked to the professional field and scientific techniques. Finally, an accounting system was designed and applied in Monica 8.5 software that was installed into the association where the transactions in 2017 period were registered, but it is suggested the record will be done at the moment they happen since it will help the records of the economic transactions into the general journal and easy access to the financial statements.